2019
DOI: 10.1021/acsomega.8b03186
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the α-l-Rhamnosidase DtRha from Dictyoglomus thermophilum: Application to the Selective Derhamnosylation of Natural Flavonoids

Abstract: α- l -Rhamnosidases are catalysts of industrial tremendous interest, but their uses are still somewhat limited by their poor thermal stabilities and selectivities. The thermophilic Dt Rha from Dictyoglomus thermophilum was cloned, and the recombinant protein was easily purified to homogeneity to afford 4.5 mg/L culture of biocatalyst. Michaelis–Menten parameters demonstrated it to be fully specific for α- l -rhamnose. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…α‐ l ‐rhamnosidases, a glycoside hydrolase, exhibit a low sequence identity at only 20%–30%, but share a similar (α/α)6‐barrel catalysis domain and several β‐sandwiches (Cui et al, 2007; Fujimoto et al, 2013; Guillotin et al, 2019; O'Neill et al, 2015; Pachl et al, 2018). Six crystal structures (PDB: 2OKX, 3W5M, 3CIH, 4XHC, 6GSZ, and 6I60) from the GH78 family have been determined so far.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…α‐ l ‐rhamnosidases, a glycoside hydrolase, exhibit a low sequence identity at only 20%–30%, but share a similar (α/α)6‐barrel catalysis domain and several β‐sandwiches (Cui et al, 2007; Fujimoto et al, 2013; Guillotin et al, 2019; O'Neill et al, 2015; Pachl et al, 2018). Six crystal structures (PDB: 2OKX, 3W5M, 3CIH, 4XHC, 6GSZ, and 6I60) from the GH78 family have been determined so far.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely used in the debittering of citrus juices (Prakash et al, 2002; Yadav & Yadav, 2000) improving the aroma components of beverages (Caldini et al, 1994; Spagma et al, 2000). To date, only 29 α‐ l ‐rhamnosidases have been biochemically characterized, and six of them, namely, Bs RhaB (PDB entry 2OKX), Bt 1001 (PDB entry 3CIH), Sa Rha78A (PDB entry 3W5M), Ko Rha (PDB entry 4XHC), At Rha (PDB entry 6GSZ), and Dt Rha (PDB entry 6I60) have been illustrated in crystal structures in GH78 family (Cui et al, 2007; Fujimoto et al, 2013; Guillotin et al, 2019; O'Neill et al, 2015; Pachl et al, 2018). In previous studies, we cloned and expressed α‐ l ‐rhamnosidase (r‐Rha1) from Aspergillus niger JMU‐TS528 (Li et al, 2016) which belongs to the GH78 family in the CAZy database.…”
Section: Introductionmentioning
confidence: 99%
“…2.1 Compactional screening the mutant candidates with better catalysis efficiency and thermostability α-L-rhamnosidases, a glycoside hydrolase, exhibit a low sequence identity at only 20%-30%, but share a similar (α/α)6-barrel catalysis domain and several β-sandwiches. [36][37][38][39][40] Six crystal structures (PDB: 2OKX, 3W5M, 3CIH, 4XHC, 6GSZ and 6I60) from the GH78 family have been determined so far. By homology modelling with the crystal structures of α-L-rhamnosidases 2OKX, 3W5M, and 4XHC as templates, the structure of r-Rha1 was built and used for our research.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 To date, only 29 α-L-rhamnosidases have been biochemically characterized, and six of them, namely Bs RhaB (PDB entry 2OKX), Bt 1001 (PDB entry 3CIH), Sa Rha78A (PDB entry 3W5M), Ko Rha (PDB entry 4XHC), At Rha (PDB entry 6GSZ), and Dt Rha (PDB entry 6I60) have been illustrated in crystal structures in GH78 family. [36][37][38][39][40] In previous studies, we cloned and expressed α-L-rhamnosidase (Rha1) from Aspergillus niger JMU-TS528, 41 which belongs to the GH78 family in the CAZy database. Simultaneously, we applied semi-conservative site-directed mutagenesis on the catalytic domain to increase the enzyme activity of Rha1.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the cloning, expression and purification of this protein [36]. As many other D. thermophilum proteins [37][38][39][40][41], DtGly was found to be thermostable and also exhibited a wide substrate specificity, as it is able to hydrolyse pNP β-D-glucoside, pNP β-D-galactoside and pNP β-D-fucoside. Moreover, our previous study demonstrated that DtGly could be used in chemoenzymatic synthesis of glycosides, thereby serving as an attractive biocatalyst that needed to be assayed for other substrates [36].…”
Section: Dtgly Can Hydrolyze Thioglycosidesmentioning
confidence: 99%